O COMÉRCIO ASSOCIADO: AS ESPECIFICIDADES DO FRANCHISING - Frade, Rui (2019)
Submitted by Domingos Martinho (domingos.martinho@islasantarem.pt) on 2019-07-16T12:42:34Z No. of bitstreams: 1 ecI2ES-2017(5).pdf: 570116 bytes, checksum: 58edc7d90913185de9f108134f9d4292 (MD5)